Implementation of telehealth during COVID-19: Implications for providing behavioral health services to pediatric patients. (June 2022) - Frye, William S; Gardner, Lauren; Campbell, Jonathan M; Katzenstein, Jennifer M
The coronavirus pandemic and in-person contact restrictions necessitated rapid implementation of telehealth, specifically videoconferencing, to provide essential care to patients. This study surveyed 25 pediatric behavioral health providers at a single center during their first month of utilizing telehealth during coronavirus disease 2019 (COVID-19). Twenty-one participants completed a pre-questionnaire distributed prior to telehealth service delivery, and 23 providers completed a post-questionnaire approximately three weeks later. Results indicate the majority of behavioral health providers had no experience providing telehealth services prior to COVID-19. The majority of participating behavioral health providers utilized telehealth to provide pediatric patient care within the first month of access to telehealth. Participants' confidence in their ability to provide telehealth services significantly increased within the first month of implementation, regardless of previous training in telehealth. This study identified differences between anticipated and actual barriers to treatment, with technological issues identified as the largest actual barrier to service delivery. Participants indicated a preference for in-person service delivery, which they reported allows for better rapport-building, behavioral observations, reduced technological barriers, and fewer distractions. However, most participants reported they intend to continue utilizing telehealth for certain types of behavioral health services (e.g., diagnostic interviews and outpatient therapy) after the pandemic has subsided.